Blood donation by male homosexuals in Brazil: the clash Supreme Court Federal x ANVISA and (in) existence of dialogue between powers - de Moraes, Maria Valentina (2021)
The 12 months period of disability after the last sexual act of men who have sex with other men and/or their partners so that they can exercise the solidarity act of blood donation was discussed by the STF in ADI 5543/DF, which understood by unconstitutionality of the regulations that brought these restrictions. After the decision, the National Sanitary Surveillance Agency issued a note to blood centers to maintain the procedure for collecting blood donations as it had been taking place before the Court’s decision. Thus, the hypothetical-deductive approach method and the analytical procedure method will be used to answer the following question: there is a dialogue between powers in relation to the position adopted by the STF in ADI 5543 and the subsequent guidance by Anvisa which recommends the maintenance of the criteria for disability for blood donation by MSMs? In conclusion, it was possible to affirm the absence of dialogue between the STF and Anvisa’s position in view of the agency’s insistence on continuing to perpetuate discriminatory conduct by issuing guidelines contrary to the precedent established by the Court in ADI 5543.